Strategi UMKM Dalam Mendorong Masyarakat Untuk Menggunakan Qris Sebagai Alat Pembayaran Digital Di Kota Bogor - Firdaus, Husni; Buono, Agus; Syarief, Rizal (Institut Pertanian Bogor, 2025)
The development of the financial technology industry in the world of fast and secure electronic, for the beginning of digital financial transaction services in various models. The research aims to provide strategic advice and recommendations to MSMEs in the food and beverage sector to encourage people to use QRIS as a digital payment tool. The research was conducted in the city of Bogor, the location was chosen purposively based on considerations of the city of Bogor as a culinary destination. Data analysis techniques are qualitative and quantitative, another analysis process is carried out on the internal and external environment using SWOT analysis, and to support the use of quantitative analysis in the IFE matrix, EFE, IE, and QSPM. Characteristics of MSMEs include the type of marketing used by gender, age, education, income, means of payment owned, length of business, reasons for using QRIS as a means of payment, price, target customers. The results of the IE matrix analysis show that food and beverage MSME business actors in Bogor City are in cell IV position with a grow and build strategy. The results of the SWOT and QSP analysis can be concluded with the main priority being to ask for support from the government (Bank Indonesia), Payment Service System Operators (PJSP) and banking in the form of promotional media support, system improvements and fee reduction support for merchants. This support motivates and encourages MSMEs to direct and advise the public and consumers to use QRIS as their first choice for transactions.